Fluorescence of living plant cells for phytomedicine preparations - Roshchina, V. V. (Boca Raton, FL : CRC Press, 2020)
Fluorescence of Living Plant Cells for Phytomedicine Preparations reveals how valuable medicinal compounds can be identified through the application of vital fluorescence in plant cells. The book explains the roles that fluorescent compounds play in plant physiology and promotes our knowledge of plant secretory cells and phytopreparations. Supported by vivid illustrations, the book reveals how actinic light light that induces fluorescence in leaves and flowers can be used in the identification of secretory cells within plant tissue that may be the repository of valuable medicinal compounds. The book demonstrates the potential of fluorescence in pharmacological analysis with detailed methods for applying fluorescence to identify these deposits of natural drugs. As such, this groundbreaking book contains methods of express-pharmaceutical analysis that could open new horizons in pharmacy and the cultivation of medicinal plants. Features Describes various fluorescence microscopy techniques for the localization of compounds contained in plants with pharmaceutical interest Provides an analysis of pharmaceutical material based on autofluorescence and histochemical reactions for numerous medicinal plant species Demonstrates practices for providing optimal growing conditions and improving the quality of the compounds Showing the readiness of plant raw material for pharmaceutical industry, this book will appeal to professionals in the pharmaceutical industry and students and researchers in the fields of phytochemistry, botany and pharmaceutical sciences.
OCLC-licensed vendor bibliographic record.
Keywords: Fluorescence; Plant luminescence; Plant cells and tissues; Plants -- Secretion; Medicinal plants; MEDICAL / Alternative Medicine; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General